Wereng Cokelat sebagai Hama Global Bernilai Ekonomi Tinggi dan Strategi Pengendaliannya - Baehaki S. E.; Made Jana Mejaya (Iptek Tanaman Pangan, 2014)
Brown planthopper (BPH) is a global rice pest, widespread in the Palaeartik, Oriental, and Australian regions. This pest had caused high losses of economic value, both as yield losses and as funds, to be used for research in the technological control. Both nymphs and adults of BPH are damaging on rice plants, through an extensive sucking of the cell sap. BPH also transmits viruses, thus increases level of BPH infestation occasionally are accompanied by substantial losses of rice crop by virus diseases resulting in hopperburn. Countries most affected by BPH attacks and had spent high number of funds to control are China, Vietnam, Thailand, Philippines, Malaysia, and Indonesia. BPH attack disrupts the nutrient uptake processes occurring on the roots, whereas the rice roots are not only playing a major role in taking up nutrients and water, but also functioning as sites for biosynthesis of substances that affect physiological activities, such as cytokinins, zeatin, and zeatin riboside. Senescence process of the leaves, transportation and distribution of assimilates, grain flling, and grain yield are closely correlated with the function of root systems of the rice plant. Strategy for BPH control includes assembling durable resistance of rice varieties using the available germplasm, tightening resistant line screening, action program such as simultaneous planting based on triangle strategies, increasing the use of light traps to monitor the populations dynamic and reducing insect populations. Control of brown planthopper using insecticides should consider the latest economic threshold, depending on the price of grain at harvest.